2006
DOI: 10.1002/jbm.a.30586
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cell adhesion and spreading by control of FnIII7–10 orientation on charged self‐assembled monolayers (SAMs) of alkanethiolates

Abstract: In this work, we demonstrate that surface charge can be used to modulate cell adhesion/spreading through the control of the orientation of adsorbed FnIII(7-10), which is a cell-adhesive protein containing RGD residues. Carboxylic acid (COOH) and amine (NH(2))-terminated self-assembled monolayers (SAMs) of alkanethiolates were used as model negatively and positively charged surfaces, respectively. The adsorbed amount of FnIII(7-10) is controlled to be equivalent on both SAMs as confirmed by the adsorption isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 26 publications
8
47
1
Order By: Relevance
“…30,33,34,36 In previous studies with MC3T3-E1 cells, it was shown that heat denatured BSA effectively prevents cell binding to TCPS and this was confirmed in this study. Additionally, in both cell binding assays, the lowest amount of cell binding was seen on -COOH terminated SAMs (0 days of HAP growth) with adsorbed BSA.…”
Section: Bsa Cell Adhesion Assaysupporting
confidence: 86%
See 1 more Smart Citation
“…30,33,34,36 In previous studies with MC3T3-E1 cells, it was shown that heat denatured BSA effectively prevents cell binding to TCPS and this was confirmed in this study. Additionally, in both cell binding assays, the lowest amount of cell binding was seen on -COOH terminated SAMs (0 days of HAP growth) with adsorbed BSA.…”
Section: Bsa Cell Adhesion Assaysupporting
confidence: 86%
“…30,31 The ability to control protein orientation with charged SAMs is mediated by the conformational stability and size of the adsorbed protein. 32,33 Other efforts have focused on utilizing specific protein-protein interactions to impart a natural biological orientation or conformation to one of the proteins. 34-36 Our previous efforts examined the MC3T3-E1 osteoblast-like cell binding onto both OPN and BSP covered surfaces when the proteins were randomly adsorbed to tissue culture polystyrene (TCPS) or specifically bound to collagen I.…”
Section: Introductionmentioning
confidence: 99%
“…Surface chemistry [37][38][39] allowed elegantly patterned neuronal networks with potentially useful functions, but long term maintenance of the networks is a problem. SAMs [40,41] represent a convenient way for engineering cell adhesion [42], as SAMs do not involve complicated instruments during the experiment. Coating is widely used for tailoring the biocompatibility of the neuron-materials interfaces [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Although this small peptide sequence is sufficient for cell adhesion, its biological activity is lower than that of the native protein owing to the absence of complementary domains such as the PHSRN (phenylalanine-histidine-serine-arginine-asparagine) sequence [15,16]. On the other hand, larger protein fragments containing such complementary sequences exhibit stronger cell adhesion and higher biological activities [17,18]. Therefore, dynamic substrates will become more physiologically relevant when used in combination with such larger protein fragments instead of the RGD peptides.…”
Section: Introductionmentioning
confidence: 99%